Nuevos espacios de solidaridad: la intervención de las ONGD españolas en el marco de la cooperación con Marruecos - Andreo Tudela, Juan Carlos (Revista Española de Desarrollo y Cooperación, 2023)
The article analyses the intervention of Spanish NGO in Morocco, since their arrival to the present, when their presence has developed much, even though they are still limited. It also studies the geographical areas in which they work (mostly in the northern area, due to historical and linguistic reasons), as well as the sectors (mostly education). It finally analyses the resources they have received from the Ministry of Foreign Affairs, to see the interest shown by Spain’s official sector in our neighbour country. Although these resources have increased, they seem to have reached now a maximum, at least concerning NGO financing.